In vitro wound healing of tumor cells: inhibition of cell migration by selected cytotoxic alkaloids - Wang, Xiaojuan; Decker, Charlotte Caroline; Zechner, Laura; Krstin, Sonja; Wink, Michael (BMC pharmacology & toxicology, 2019)
Cell migration is involved in several pathological processes such as tumor invasion, neoangiogenesis and metastasis. Microtubules are needed in directional migration.